Photography among the Arabs before Islam Preparation - Aziz, Janan Ahmed Abdel (Journal of Posthumanism, 2025)
In this research, the topic of photography among Arabs before Islam was addressed, and the importance of this topic was centered on the scarcity of studies that dealt with it, within the limits of the researcher’s knowledge, and the topic of photography among Arabs was addressed by description and analysis of all books and opinions that focused on many of its aspects, after the study was divided into two researchers, the first research dealt with: the reality of photography among Arabs before Islam, and then through the second research dealt with models of photography among Arabs before Islam. The study found that photography among Arabs was characterized by an Arab character that reflected the reality and environment of the Arabian Peninsula in particular, which was reflected in the decorated features of the people depicted in the statues. Arab photographers, like engravers, also embodied cult statues in the form of a human or animal. The drawings depicted on the walls of the Kaaba showed the interest of pre-Islamic Arabs in the art of photography. The Arabs of pre-Islamic Arabia also embodied images through the manufacture of statues, showing the diversity of style and subject matter. Stone sculptures in pre-Islamic Arabia were distinguished by being more realistic, more accurate and smaller in size. Metal figurines appeared in pre-Islamic Arabia more liberally than traditional stone figurines.